Camp Pliley, Pottersburg, and Ash Grove, Lincoln County - Lupfer-Nielsen, Kathryn (Kansas State University, The Chapman Center for Rural Studies, 2012)
The lost communities of Camp Pliley, Pottersburg and Ash Grove, Kansas were settled by Civil War Veterans, Scandinavian immigrants as well as homesteading pioneers. While Pottersburg and Ash Grove locations achieved railroad service, the automobile caused the communities to shrink, one room schools and businesses to close as well as the rural churches to dissolve. The study will look at census records, newspaper articles, early history as well as maps for the camp and the townships.
Kathryn Lupfer-Nielsen, “Camp Pliley, Pottersburg, and Ash Grove, Lincoln County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/94.
Keywords: Ash Grove; Barnard; Camp Pliley; Lincoln County; Pottersburg; Bacon Creek